Produção de milho doce sob fontes e doses de nitrogênio em associação à Azospirillum brasilense. - Barros, Daline Taynã Santos (2019)
Sweet corn has attractive sensory characteristics for consumption, growing in the form of green maize, whether in natura or industrialized. However, the technical information regarding sweet corn is still scarce, especially those related to inoculation with growth promoting bacteria in substitution for nitrogen fertilization. The objective of this study was to evaluate the effect of different sources and nitrogen levels in association with inoculation of seeds with bacteria in the agroeconomic yield of sweet corn. The experiment was conducted in the experimental area of the Hada / Asa Branca Industry, located in the municipality of Arapiraca-AL. The experimental design was a randomized complete block design with twenty four treatments and four replications. The plots consisted of four nitrogen doses (0, 50, 100 and 150 kg ha-1 of N) and six nitrogen sources in association with the inoculation of the bacterium Azospirillum brasilense - AZOS (calcium nitrate with AZOS, ammonium sulfate with AZOS, urea with AZOS, calcium nitrate without AZOS, ammonium sulfate without AZOS and urea without AZOS). The agronomic and industrial evaluations were constituted by: green index; plant height and spike insertion; stem diameter; weight, diameter and length of spike with and without straw; width and depth of grains; grain weight; weight of cob; brix; pH and grain and ear yield per hectare. The obtained data were submitted to analysis of variance to verify the test f and the means studied through the polynomial regression analysis, with the aid of the statistical program Sisvar. The nitrogen sources used do not interfere with the performance of sweet corn plants. The dose of 117 kg ha-1 of N provides an increase in productivity of sweet corn plants. The inoculation of sweet corn seeds with the Azospirillum brasilense bacterium does not interfere with the yield of sweet corn grains.